The Existence of Nahdlatul Ulama Cadre Education (PKPNU) in Banten and Its Surrounding Areas - Agus Pramono; Moebi Syahirul Alim (Lakpesdam PCNU Kota Salatiga, 2022)
Nahdlatul Ulama Cadre Education (PKPNU) is one of Nahdlatul Ulama (NU) cadre regeneration activities to instill Ahlus Sunnah wal Jamaah values. Ideologically, it is a concrete step to form qualified cadres with organizational governance skills and as one of the capitals in developing NU to be an increasingly efficient organization. PKPNU is manifested throughout Indonesia, where some regions have different characteristics. In Banten, PKPNU is managed by NU cadres as the reference for Ulama Qhos, or charismatic kyaiâ€”supported by cadres or santri trusted by the charismatic ulama throughout Banten. All activities are organized by a committee approved by PCNU in Banten Region because the speakers come from charismatic kyai recommended by PCNU in Banten Region. It differs from other regions as one presenter is Rais Syuriah of PCINU in the Russian Federation and the Northern European Region. It distinguishes the PKPNU program from other regions because there is a very progressive addition to the content of PKPNU material, one of which is often conveyed in the preamble, namely the preparation of the Nahdliyin generation in facing the global challenges of the industrial revolution 4-5.Â